Icariin protects vertebral endplate chondrocytes against apoptosis and degeneration via activating Nrf-2/HO-1 pathway - Shao, Yuandong; Sun, Lei; Yang, Guihe; Wang, Wenchao; Liu, Xiaoyang; Du, Ting; Chen, Feifei; Jing, Xingzhi; Cui, Xingang (Frontiers in Pharmacology, 2022)
Cartilage endplate (CEP) plays important roles in the onset and progression of intervertebral disc degeneration (IVDD). Icariin (ICA) is the major active ingredient of Herba Epimedii and has various biological activities such as anti-inflammatory and antioxidant, which is used to treat many degenerative diseases. However, the effects and mechanism of ICA on endplate chondrocytes are still unclear. Herein, we studied the effects of ICA on CEP degeneration and elucidated the underlying mechanisms. Endplate chondrocytes were isolated, and TNF-α and TBHP were applied to mimic an IVDD pathological environment. Also, an IVDD mice model was established by transection of bilateral facet joints to investigate the protective effect of ICA in vivo. We found that ICA treatment inhibited the chondrocytes apoptosis and the decrease of extracellular matrix production in a dose-dependent manner. Our in vivo experiments demonstrated that ICA could ameliorate IVDD development and CEP calcification. We also found that the ICA-activated Nrf-2/HO-1 pathway thus promoted the Parkin-mediated mitophagy process and inhibited chondrocytes ferroptosis, thus alleviated redox imbalance and mitochondrial dysfunction and eventually improved cell survival. Knockdown of Nrf-2 using siRNA reversed the protective effect of ICA on endplate chondrocytes apoptosis and degeneration. In conclusion, our study demonstrated that ICA could protect against CEP degeneration and calcification under IVDD pathological conditions, the associated mechanism may be related to Nrf-2/HO-1-mediated mitophagy activation and ferroptosis inhibition. Our results suggest that ICA may be a potential effective medicine for IVDD prevention and treatment.